2015
DOI: 10.4236/fns.2015.615149
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Seasons on Theanine Levels in Different Kenyan Commercially Released Tea Cultivars and Its Variation in Different Parts of the Tea Shoot

Abstract: A study was conducted to determine the effect of seasons in 23 different Kenyan commercially released tea cultivars. This was done for three seasons viz: cold and wet, cold and humid, hot and dry. The cold and wet season was shown to be the best for obtaining high levels of theanine while the hot and dry season resulted in decrease in theanine levels in most of the test cultivars thus showing seasonal variation on the levels of theanine. Theanine content was determined using High Performance Liquid Chromatogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…As one of the most important components of quality in green tea, theanine and its biosynthesis has been studied intently in tea plants since it was discovered by Yajiro Sakato in 1949 (Ashihara, 2015; Mu et al, 2015). These studies indicated that theanine accumulation was dynamically regulated by seasons (Konishi and Takahashi, 1969; Takeo, 1981; Janet et al, 2015), light (Yang et al, 2012; Deng et al, 2013; Chen et al, 2017; Ji et al, 2018; Sano et al, 2018), nutrient levels (Takeo, 1981; Ruan et al, 2007; Ruan et al, 2010; Ruan et al, 2012; Huang et al, 2018; Kc et al, 2018; Zhu et al, 2019), hormones (Li et al, 2016a), developmental stages (Feldheim et al, 1986; Li et al, 2016b; Liu et al, 2017), and stress (Deng et al, 2012; Wang et al, 2016). Theanine accumulation is also highly tissue-and cultivar-dependent (Fang et al, 2017; Liu et al, 2017; Chen et al, 2018a; Chen et al, 2018b).…”
Section: Discussionmentioning
confidence: 99%
“…As one of the most important components of quality in green tea, theanine and its biosynthesis has been studied intently in tea plants since it was discovered by Yajiro Sakato in 1949 (Ashihara, 2015; Mu et al, 2015). These studies indicated that theanine accumulation was dynamically regulated by seasons (Konishi and Takahashi, 1969; Takeo, 1981; Janet et al, 2015), light (Yang et al, 2012; Deng et al, 2013; Chen et al, 2017; Ji et al, 2018; Sano et al, 2018), nutrient levels (Takeo, 1981; Ruan et al, 2007; Ruan et al, 2010; Ruan et al, 2012; Huang et al, 2018; Kc et al, 2018; Zhu et al, 2019), hormones (Li et al, 2016a), developmental stages (Feldheim et al, 1986; Li et al, 2016b; Liu et al, 2017), and stress (Deng et al, 2012; Wang et al, 2016). Theanine accumulation is also highly tissue-and cultivar-dependent (Fang et al, 2017; Liu et al, 2017; Chen et al, 2018a; Chen et al, 2018b).…”
Section: Discussionmentioning
confidence: 99%
“…The more tender the tea stems were, the greater the theanine content they had. Theanine content may decrease with the tenderness of tea stems because of the enzymatic breakdown of theanine into Glu and ethylamine increases as stems mature [ 42 ]. This process increases not only sweetness but also amino acid content and facilitates the generation of heterocyclic aromatic compounds in roasting processes [ 43 , 44 ], thereby improving the flavor of the tea and its robustness to UHT sterilization.…”
Section: Resultsmentioning
confidence: 99%
“…In line with our results, Too et al reported theanine level in the range between 1.4 and 15.0 mg g À1 in green tea manufactured from Kenyan tea cultivars using HPLC. 36 Kilel et al reported a higher level of theanine (15.0-21.8 mg g À1 ) in green tea processed from purple tea cultivars of Kenya. 18 Theanine content in Longjing green tea varied between 5.68 and 17.36 mg g À1 .…”
Section: Theaninementioning
confidence: 97%